Penerapan Konsep Tropical Calm pada Desain Interior Lobby Fivestar Family Reflexology untuk Healing Therapy - Aldea Risma Septiawati; Erwin Rezasyah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The lobby is the initial area that forms impressions and serves as a transition zone before visitors undergo reflexology therapy. Often, lobby designs that ignore psychological aspects and circulation placement can reduce the overall effectiveness of the healing process. This study aims to analyze the implementation of the Tropical Calm concept in the interior of the Family Reflexology lobby, with a case study at Fivestar Reflexology, as a supporting element of healing therapy. The research method used is descriptive qualitative, evaluating interior elements through literature review and direct field surveys. The results of the study show that in addition to the synergy of natural materials and tropical color palettes, the strategic zoning of the reception area is crucial in creating a comfortable spatial orientation for users. The integration of appropriate Tropical Calm elements has been proven effective in reducing initial stress levels and supporting the holistic relaxation process for visitors from the moment they enter the building.